PENGARUH UMUR DAUN TEH DAN WAKTU OKSIDASI ENZIMATIS TERHADAP KANDUNGAN TOTAL FLAVONOID PADA TEH HITAM (Camellia sinesis) - Jennifer Larisa Liem; Maria Marina Herawati (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
Flavonoid compound is an important compound of tea products. However, the flavonoid level content in black tea is lowest than other teas. This is due to the processing of black tea which has an enzymatic oxidation stage and  the tea age leaves when picking. Young tea leaves contain higher total flavonoids than old tea leaves. With an average level of total flavonoids, the young tea leaves is 27.76% qe w / w, while for the old tea leaves 18.61% qe w / w. However, the enzymatic oxidation time treatment did not affect the total flavonoids because the process only affected the quality of black tea steeping, on it’s colour, aroma, and taste. Keywords: age of tea leaves, black tea, enzymatic oxidation, total flavonoids